Proceedings of the 5th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2015
DOI: 10.7712/120115.3398.460
|View full text |Cite
|
Sign up to set email alerts
|

Collapse Risk Evaluation of Self-Centering Steel MRFS With Viscous Dampers in Near-Fault Regions

Abstract: Abstract. This paper presents an evaluation of the seismic collapse risk of self-centering moment-resisting frames (SC-MRFs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Collapse risk of self-centering systems in moment-resistant frames as well as the probability of exceeding the inter-story drifts were other components that were covered by researchers. By conducting different incremental dynamic analyses (IDA) in near-eld regions, it was observed that the probability of collapsing and exceeding the inter-story threshold, signi cantly decreases when using post-tensioning elements and viscous dampers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Collapse risk of self-centering systems in moment-resistant frames as well as the probability of exceeding the inter-story drifts were other components that were covered by researchers. By conducting different incremental dynamic analyses (IDA) in near-eld regions, it was observed that the probability of collapsing and exceeding the inter-story threshold, signi cantly decreases when using post-tensioning elements and viscous dampers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%